Cardiac nuclear high mobility group box 1 prevents the development of cardiac hypertrophy and heart failure - Funayama, Akira (Oxford University Press, 2013)
AIMS: High mobility group box 1 (HMGB1) is an abundant and ubiquitous nuclear DNA-binding protein that has multiple functions dependent on its cellular location. HMGB1 binds to DNA, facilitating numerous nuclear functions including maintenance of genome stability, transcription, and repair. However, little is known about the effects of nuclear HMGB1 on cardiac hypertrophy and heart failure. The aim of this study was to examine whether nuclear HMGB1 plays a role in the development of cardiac hypertrophy induced by pressure overload. METHODS AND RESULTS: Analysis of human biopsy samples by immunohistochemistry showed decreased nuclear HMGB1 expression in failing hearts compared with normal hearts. Nuclear HMGB1 decreased in response to both endothelin-1 (ET-1) and angiotensin II (Ang II) stimulation in neonatal rat cardiomyocytes, where nuclear HMGB1 was acetylated and translocated to the cytoplasm. Overexpression of nuclear HMGB1 attenuated ET-1 induced cardiomyocyte hypertrophy. Thoracic transverse aortic constriction (TAC) was performed in transgenic mice with cardiac-specific overexpression of HMGB1 (HMGB1-Tg) and wild-type (WT) mice. Cardiac hypertrophy after TAC was attenuated in HMGB1-Tg mice and the survival rate after TAC was higher in HMGB1-Tg mice than in WT mice. Induction of foetal cardiac genes was decreased in HMGB1-Tg mice compared with WT mice. Nuclear HMGB1 expression was preserved in HMGB1-Tg mice compared with WT mice and significantly attenuated DNA damage after TAC was attenuated in HMGB1-TG mice. CONCLUSION: These results suggest that the maintenance of stable nuclear HMGB1 levels prevents hypertrophy and heart failure by inhibiting DNA damage.